Functional Characterization of Novel Faecalibacterium prausnitzii Strains Isolated from Healthy Volunteers: A Step Forward in the Use of F. prausnitzii as a Next-Generation Probiotic - Martín, Rebeca; Miquel, Sylvie; Benevides, Leandro; Bridonneau, Chantal; Robert, Véronique; Hudault, Sylvie; Chain, Florian; Berteau, Olivier; Azevedo, Vasco; Chatel, Jean M.; Sokol, Harry; Bermúdez-Humarán, Luis G.; et al. (Frontiers in Microbiology, 2017)
Faecalibacterium prausnitzii is a major member of the Firmicutes phylum and one of the most abundant bacteria in the healthy human microbiota. F. prausnitzii depletion has been reported in several intestinal disorders, and more consistently in Crohn’s disease (CD) patients. Despite its importance in human health, only few microbiological studies have been performed to isolate novel F. prausnitzii strains in order to better understand the biodiversity and physiological diversity of this beneficial commensal species. In this study, we described a protocol to isolate novel F. prausnitzii strains from feces of healthy volunteers as well as a deep molecular and metabolic characterization of these isolated strains. These F. prausnitzii strains were classified in two phylogroups and 3 clusters according to 16S rRNA sequences and results support that they would belong to two different genomospecies or genomovars as no genome sequencing has been performed in this work. Differences in enzymes production, antibiotic resistance and immunomodulatory properties were found to be strain-dependent. So far, all F. prausnitzii isolates share some characteristic such as i) the lack of epithelial cells adhesion, plasmids, anti-microbial and hemolytic activity and ii) the presence of DNAse activity. Furthermore, Short Chain Fatty Acids (SCFA) production was assessed for the novel isolates as these products influence intestinal homeostasis. Indeed, the butyrate production has been correlated to the capacity to induce IL-10, an anti-inflammatory cytokine, in peripheral blood mononuclear cells (PBMC) but not to the ability to block IL-8 secretion in TNF-α-stimulated HT-29 cells, reinforcing the hypothesis of a complex anti-inflammatory pathway driven by F. prausnitzii. Altogether, our results suggest that some F. prausnitzii strains could represent good candidates as next-generation probiotic.